Caracterização de desafios e estratégias de teste para sistemas adaptativos - Siqueira, Bento Rafael (2016)
Context: Traditional testing approaches, considering the context of Adaptive Systems (ASs), have been evaluated incipiently and superficially with respect to their effectiveness in identifying faults. It is very clear the challenge of guaranteeing the correctness of ASs, due to the adaptive properties of these systems. Thus, the following question raises: how to characterise adequately and broadly the difficulties for testing ASs? There is not an approach that is driven by challenges found in the literature. Goals: In this work, we analysed and characterised the challenges faced by the testing activity when applied to ASSs. By characterising the challenges, we investigated testing strategies based on them. Methodology: In order to achieve the goals, we performed the following steps: (i) characterising the state-of-art of testing of ASs, using a Systematic Literature Review (SLR); (ii) investigating the challenges in source codes of real ASs that are available online in source code repositories; (iii) defining the testing strategy named T, based on the characterised challenges; (iv) defining the testing strategy T* based on the challenges and comprised by three testing approaches; (v) evaluating the effectiveness of the strategies T and T*; and (vi) investigating the challenges along the application of T and T*. Results: the main results were: (i) a characterisation of fine-grained and coarse-grained challenges for testing ASs; and (ii) two testing strategies based on such challenges. We evaluated the strategies by running an exploratory study which encompassed one AS and both testing strategies. Conclusion: The characterisation of challenges supported the definition and execution of the testing strategies. These strategies were able to reduce the impact of the challenges and to identify faults in the AS.